2015
DOI: 10.3892/mmr.2015.4634
|View full text |Cite
|
Sign up to set email alerts
|

4.1N suppresses hypoxia-induced epithelial-mesenchymal transition in epithelial ovarian cancer cells

Abstract: Protein 4.1N (4.1N) is a member of the protein 4.1 family and is essential for the regulation of cell adhesion, motility and signaling. Previous studies have suggested that 4.1N may serve a tumor suppressor role. However, the molecular mechanisms remain unclear. In the current study, the role of 4.1N in the downregulation of hypoxia‑induced factor 1α (HIF‑1α) under hypoxic conditions and therefore the suppression of hypoxia induced epithelial‑mesenchymal transition (EMT) was investigated. The data were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…4.1N is a member of the 4.1 protein family and is involved in cell migration and adhesion [7]. Increasing research has shown that 4.1N also plays an important role in several cancers [8][9][10]. For kidney cancer, in a previous study, Nagata et al found that CADM4 was connected to 4.1B, and CADM1 was connected to 4.1N in human normal kidney.…”
Section: Discussionmentioning
confidence: 99%
“…4.1N is a member of the 4.1 protein family and is involved in cell migration and adhesion [7]. Increasing research has shown that 4.1N also plays an important role in several cancers [8][9][10]. For kidney cancer, in a previous study, Nagata et al found that CADM4 was connected to 4.1B, and CADM1 was connected to 4.1N in human normal kidney.…”
Section: Discussionmentioning
confidence: 99%
“…[7]. Increasing research has shown that 4.1N also plays an important role in several cancers [8][9][10]. For kidney cancer, in a previous study, Nagata et al found that CADM4 was connected to 4.1B, and CADM1 was connected to 4.1N in human normal kidney.…”
Section: App Expression In Kirc Patientsmentioning
confidence: 98%
“…Just like other protein 4.1 family members, 4.1N as a bridge connecting actin cytoskeleton and various transmembrane proteins, plays a key role in cell invasion, migration, and adhesion [8]. It has been reported that protein 4.1N plays an important role in the development of tumors such as breast [8] and ovary cancer [9,10]. For human kidneys, previous study has shown that 4.1N associated with the cell adhesion molecule CADM1 expresses in distal tubules.…”
Section: Introductionmentioning
confidence: 99%
“…1N is a member of the 4.1 protein family and is involved in cell migration and adhesion [7]. Increasing research has shown that 4.1N also plays an important role in several cancers [8][9][10]. For kidney cancer, in a previous study, Nagata et al found that CADM4 was connected to 4.1B, and CADM1 was connected to 4.1N in human normal kidney.…”
Section: App Expression In Kirc Patientsmentioning
confidence: 99%